Pengaruh Harga, Servicescape, Kualitas Produk Dan Store Atmosphere Terhadap Keputusan Pembelian Konsumen Di Putri Shop Kotapinang - Dalimunthe, Ali Sahputra (Universitas Labuhanbatu, 2021)
This study aims to examine the effect of price, Servicescape, product quality and store atmosphere on purchasing decisions in Putri Shop Kotapinang, South Labuhanbatu Regency. Data collection was carried out by distributing questionnaires and distributed to 70 research samples, namely Putri shop kotapinang consumers. Data analysis in this study using the help of SPSS version 20. Data testing techniques conducted in this study include validity and reliability test, classical assumption test, multiple linear regression analysis, and partial and simultaneous testing. The results showed that the price has a positive effect on the purchase decision it can be seen from the value of t count > t table (3,404>1,997), servicescape has a positive effect on the purchase decision it can be seen from the value of t count > t table (2,260>1,997), product quality has a positive effect on the purchase decision it can be seen from the value of t count > t table (4,259>1,997), store atmosphere has a positive effect on the purchase decision it can be seen from the value of t count > t table (2,104>1,997), price, ServiceScape, product quality and storeatmosphere together have a positive effect on the purchase decision this can be seen from the value of F count > F table (97,562 > 2,51).